2017
DOI: 10.1016/j.whi.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding High Utilization of Unscheduled Care in Pregnant Women of Low Socioeconomic Status

Abstract: Background Pregnant high utilizers of unscheduled care may be at particular risk for poor perinatal outcomes, but the drivers of this association have not been explored from the patient perspective. Purpose We sought to understand maternal preference for unscheduled hospital-based obstetric care to inform interventions and improve value of publicly funded care during pregnancy. Methods We conducted a comparative qualitative analysis of in-depth semistructured interviews. Low-income pregnant women presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…The PGOMPS does not measure health care quality, but rather satisfaction with the process of outpatient health care provision. It is important to make the distinction between quality and satisfaction, particularly when interpreting evidence suggesting that social deprivation may in uence a patient's perception of the care they received (22,(62)(63)(64)(65). Along those lines, this study does not address the underlying causes of differences in patient satisfaction scores between patients with different levels of social deprivation.…”
Section: Discussionmentioning
confidence: 97%
“…The PGOMPS does not measure health care quality, but rather satisfaction with the process of outpatient health care provision. It is important to make the distinction between quality and satisfaction, particularly when interpreting evidence suggesting that social deprivation may in uence a patient's perception of the care they received (22,(62)(63)(64)(65). Along those lines, this study does not address the underlying causes of differences in patient satisfaction scores between patients with different levels of social deprivation.…”
Section: Discussionmentioning
confidence: 97%
“…The PGOMPS does not measure health care quality, but rather satisfaction with the process of outpatient health care provision. It is important to make the distinction between quality and satisfaction, particularly when interpreting evidence suggesting that social deprivation may influence a patient’s perception of the care they received [ 22 , 62 65 ]. Along those lines, this study does not address the underlying causes of differences in patient satisfaction scores between patients with different levels of social deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, higher unscheduled health‐care utilization, but not inadequate prenatal care receipt, was associated with postpartum overdose. A qualitative study of low‐income pregnant women with high unscheduled care found that utilization may be driven by experiences of illness insufficiently addressed by out‐patient prenatal care . The experience of women having unmet health needs may portend future postpartum overdose risk, regardless of whether or not a diagnosis of OUD is identified at delivery.…”
Section: Discussionmentioning
confidence: 99%